1994
DOI: 10.1038/npp.1994.19
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Effects on the Spontaneous Electroencephalogram in Polydrug Abusers: Correlations with Subjective Self-Reports

Abstract: The spontaneous electroencephalogram (EEG) was recorded after the intramuscular (IM) injection of morphine sulfate (15, 30 mg) or saline (0.9% NaCl). Correlations between changes in EEG spectral power and subjective self-reports, as measured on subscales of the Addiction Research Center Inventory (ARC!), were evaluated. Morphine increased alphaJ and alpha2 power and theta power, and attenuated the increase in delta power observed after placebo. Positive correlations were found between the change in alpha1, alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Third, different opioids such as morphine and fentanyl can produce markedly different EEG patterns. For instance, Phillips et al (1994) found that morphine primarily affected alpha-band but not delta-band activity in heroin abusers, whereas in the present study fentanyl primarily affected delta-band but not alpha-band activity.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…Third, different opioids such as morphine and fentanyl can produce markedly different EEG patterns. For instance, Phillips et al (1994) found that morphine primarily affected alpha-band but not delta-band activity in heroin abusers, whereas in the present study fentanyl primarily affected delta-band but not alpha-band activity.…”
Section: Discussioncontrasting
confidence: 36%
“…Morphine-like drugs can increase EEG power in the delta (0.35-3.5 Hz) and theta frequency range (3.5-8 Hz) or decrease power in the alpha-band range (8-13 Hz) in awake, opioid-abusing individuals (Fink et al, 1971;Phillips et al, 1994;Volavka et al, 1970). Experimenter-administered fentanyl and other short-acting mu-opioid analgesics primarily increase delta-band power in surgical patients (Bovill et al, 1983;Scott et al, 1991;Sebel et al, 1981;Wauquier et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…These two affect processed EEG in the same way at these concentrations [24], thus excluding a major difference between drugs on monitoring and excluding a major impact on our results. Morphine infusion may also interfere with processed EEG [11,25,26]. However, the doses of morphine administrated were low and identical in the two study groups and were not modified during the study period.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Negative consequences of disrupted sleep include an enhanced sensitivity to pain (Onen et al, 2001a, Onen et al, 2001b, Kundermann et al, 2004, Roehrs et al, 2006 and deficits in daytime performance leading to an increased risk of accidents (reviewed in Durmer and Dinges, 2005). Opioids disrupt wakefulness by causing impaired cognitive and psychomotor function (Clemons et al, 1996, Sjogren, 1997 and by increasing slow frequencies in the cortical electroencephalogram (EEG) (Volavka et al, 1970, Sebel et al, 1981, Wauquier et al, 1984, Scott et al, 1991, Phillips et al, 1994, Greenwald and Roehrs, 2005. Preclinical studies also show that systemic opioid administration disrupts deep sleep, inhibits REM sleep, and slows the cortical EEG during wakefulness (Colasanti and Khazan, 1973, King et al, 1981, de Andres et al, 1984, MayoMichelson and Young, 1993, Arankowsky-Sandoval and Gold, 1995, Osman et al, 2005.…”
mentioning
confidence: 99%